Building data visualizations for CT/MRI volumetric analysis - Lim, Kai Sheng (Nanyang Technological University, 2024)
This project aims to create an intuitive and informative visualization from CT, MRI, DTI, and fMRI images to enhance healthcare professionals' diagnostic and research capabilities.